ON THE CLINICAL SIGNIFICANCE OF FACTORS PREDICING THE DEVELOPMENT OF PATHOLOGY OF THE ESOPHAGUS AND STOMACH IN BRONCHIAL ASTHMA (Eureka Journal of Health Sciences & Medical Innovation, 2026)
The article presents the results of studying the frequency and nature of esophageal and gastric lesions in bronchial asthma patients and assessing causal risk factors for their development and criteria for predicting their formation. The regimens for administering glucocorticosteroid therapy (GCS) for bronchial asthma and the daily doses of GCS were closely related to the clinical manifestations of the lesions. Smoking, alcohol consumption, consumption of very cold drinks, incorrect use of inhalers, body mass index over 30, use of systemic glucocorticosteroids at doses exceeding 10 mg/day and their prolonged use for more than 5 years, as well as the use of inhaled glucocorticosteroids at doses exceeding 1000 mcg/day and their prolonged use for more than 5 years are important prognostic factors. These factors significantly increase the likelihood of developing gastric and esophageal diseases.
Keywords: Bronchial asthma, glucocorticosteroids, esophageal and gastric damage, prognostic predictors